Study on the antioxidant and antimicrobial properties of pink guava leaves and seeds and their effects on the shelf life of cookies / Wan Nur Zahidah Wan Zainon - Wan Zainon, Wan Nur Zahidah (2012)
This research consists of two parts. The first part is to study the antioxidant and antimicrobial properties of pink guava leaves and seeds aqueous extracts. The samples were investigated for their antioxidant activities (AOA) employing various established in vitro assays such as total phenolic content (TPC). total flavonoid content (TFC). ferric-reducing antioxidant power (FRAP). l,l-diphenyl-2-picrylhydrazyI (DPPH) free radical-scavenging ability. (3-carotene bleaching assay and Oxygen Radical Absorbance Capacity (ORAC). Oxidative stability using accelerated study in the fat system was also conducted using Rancimat method. From the study, guava leaves extract had the highest TPC and TFC than guava seeds extracts. Guava leaves extract exhibited strong efficiency and showed over 90% scavenging effect of DPPH at a concentration of 200 Hg/ml. The inhibition of lipid peroxidation of BHA/BHT by using (3-carotene bleaching assay was significantly higher than all plant extracts tested. In accelerated study using rancimat method, addition of natural extracts exerted potent antioxidant effects in retarding fat oxidation which was comparable to BHA/BHT combination. From this study, the antioxidant activity of pink guava leaves and seeds were found to increased proportionally with total phenolic content. Correlations between total phenolic content and antioxidant activity were investigated. The identification of flavonoids was also determined by using HPLC. Two types of flavonoids detected in guava leaves extract were myricetin (95.894± 2.8 mg/g extract) and quercetin (70.022± 7.1 mg/g extract) while in guava seeds extracts, only catechin was detected (247.442 ± 36.3 mg/g extract). Antimicrobial test using disc diffusion method was employed. Guava leaves extracts displayed a stronger antimicrobial effect against gram positive bacteria (S. aureus and B. sublilis). The second part of the study is to evaluate the effect of guava leaves and seeds extracts on the shelf life of cookies stored at room temperature for 3 months. Seven formulations consisted of: control sample (cookies without addition of antioxidant) (Fl), cookies with BHA/BHT extract (F2). with 100 ppm leaves extract (F3), with 200 ppm leaves extract (F4), with 900 ppm seeds extract (F5). with 1300 ppm seeds extracts (F6) and with combination of 100 ppm leaves and 100 ppm seeds extracts (F7). Results for oxidative stability tests on the cookies using Peroxide Value (PV) and Thiobarbituric Acid (TBA) showed that all samples added with plant extracts and BHA/BHT slowed down the rate of peroxide formation throughout the storage period. All samples were able to maintain PV less than 10 mEq/kg until 12 weeks of storage. For yeast and mould count, addition of plant extracts and BHA/BHT were able to delay the growth of yeast and mould until week 8. From the sensory evaluation tests conducted on the samples, the presence of plant extracts in the cookies formulations were not detected by the panelists.